THEORETICAL ASPECTS OF LEXIS OF “SURPRISE” IN THE UZBEK AND ENGLISH LANGUAGES - Xayrulla Toshquvvatov Lutfulla o´g´li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article highlights the study and theoretical aspects of lexical units related to surprise in English and Uzbek, presenting and analyzing scientific views on this topic through examples.